Law Review of Islamic Capital Market Role to Support Sustainable Economic Development - Helza Nova Lita; Zahera Mega Utama (Tazkia Islamic Finance and Business Review, 2013)
Objective - The objective of this paper is to assess on how the rule of Islamic capital markets to support   sustainable economic development and what kind of instruments can be developed.Method – The method used in this research is the study of normative juridical approach to legislation and the concept of Islamic economics through literature review.Result – Issuer's business activities related to support for environmentally friendly business activities are part of the implementation of sharia principles despite the provisions of the implementation of Islamic finance through a decision has not been stated . All types of instruments issued by issuers of sharia in Indonesia should be consistent with Islamic economic values, including the commitment to enforcement of environmentally friendly business activities.Conclusion – This finding suggests to strengthen the legal instruments in the issuer's issuance of Islamic instruments in the form of regulations issued by the Securities and Exchange Commission  and through the National Fatwa Council of Sharia.Keywords : Islamic Capital Markets, sustainable economic development, friendly environment